Virtual Tour Research Trends in Education: A Systematic Literature Review and Bibliometric Analysis Using Bibliometrix R and Biblioshiny - Yahya Gunawan; Melva Zainil (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study systematically examines the landscape of virtual tour research in education from 2020 to 2026 using a combined approach of systematic literature review and bibliometric analysis with Bibliometrix R and Biblioshiny. The research aims to identify publication trends, conceptual and thematic structures, intellectual patterns, and research gaps. Data were collected from Scopus-indexed journal articles, filtered using inclusion and exclusion criteria, and analyzed through co-citation, co-occurrence, and thematic mapping. Results indicate rapid growth in publication volume, from 22 articles in 2020 to 135 in 2025, with interdisciplinary contributions spanning tourism, cultural heritage, urban studies, and educational technology. Intellectual and conceptual structures remain fragmented, with dominant themes on tourism, heritage, and facility-oriented training, whereas pedagogical strategies, assessment, and learning transfer are underexplored. Keyword co-occurrence reveals a reliance on virtual reality frameworks while emerging themes include responsible AI, digital twins, and ethics, suggesting a shift toward socially and ethically informed research directions. Findings highlight that virtual tours have transitioned from niche technological tools to integral pedagogical instruments, yet pedagogical applications require further consolidation. The study contributes to the field by mapping research evolution, identifying knowledge gaps, and guiding future research agendas toward systematic, pedagogically beneficial applications in education.